AN ANALYSIS OF ENGLISH ONOMATOPOEIA IN DOG MAN: BIG JIM BEGINS COMIC BY DAV PILKEY - Tias Septiani; Suardi (Pojok Publisher, 2026)
This study examines the application of onomatopoeia in Dog Man: Big Jim Begins, utilizing the classification proposed by Körtvélyessy and Štekauer (2024) in Onomatopoeia in the World’s Languages. A qualitative descriptive technique discovered and categorized 87 samples into the following groups: water (5), air (11), mammals (2), body (26), vehicles (2), tools of war and destruction (26), and mechanical and electronic equipment and devices (15). Auditory signals from the body and instruments of war and destruction were predominant. Findings demonstrate that onomatopoeia substantially enriches the comic's ambiance, depicts activities, and communicates character emotions, so rendering the narrative more captivating and comprehensible. This comprehensive taxonomy provides profound insights into how sound effects enhance storytelling in comics.